Study on the characteristics of international coal trade on complex network - Xiaoci Chen; Zhanglu Tan; Siwen Li (Journal of Business Economics and Management (JBEM), 2022)
This paper builds a complex network of weighted and directed coal trade based on the international coal trade data in the United Nations trade database from 1999 to 2018, specifically analyzes the trade scale, trade relations, and trade distribution and other characteristics of international coal trade, and determines the main trade core countries and trade hub countries. The results show that the scale of international coal trade has grown steadily, but the transformation of trade relations is complicated. Especially in the context of increasing trade frictions, trade links between countries have decreased significantly, trade balance has declined, and trade agglomeration has increased. Australia, the United States, Japan and other countries are big coal trading countries, while the United States, South Africa, India and other countries are important trading hubs. Based on the theory of competitive advantage, this paper proposes corresponding countermeasures for different countries to enhance their competitive advantages.
Keywords: F02; F14; F23; 650; international coal trade; complex network; trade scale; trade relations; trade distribution; trade core countries; trade hub countries